1980
DOI: 10.1007/bf02391205
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural lesions of retinal pericapillary Müller cells in streptozotocin-induced diabetic rats

Abstract: Seventeen Wistar inbred rats were made diabetic by a single injection of streptozotocin (50 mg/kg body weight) and were killed after periods of 3, 6, 9 or 12 months. Pathological changes in pericapillary Müller cells of the retina were studied using electron microscopy. Basement membrane-like material proliferated in the intercellular space of the Müller cell network and occasionally appeared to insinuate into the Müller cell cytoplasm far from capillary pericytes and endothelial cells. The part of the Müller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 13 publications
1
16
0
1
Order By: Relevance
“…Based on these results and considering that the phagocytic character of Müller cells manifested only in the NFL, it is highly likely that the debris from the delayed degeneration of nerve fibers is cleared by activated Müller end feet. This proposition remains equivocal, even though in vitro studies have reported a phagocytic function for Müller cells [38,39], and ultrastructural studies an increased lysosomal content in the Müller cells of streptozotocin-induced diabetic rats [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results and considering that the phagocytic character of Müller cells manifested only in the NFL, it is highly likely that the debris from the delayed degeneration of nerve fibers is cleared by activated Müller end feet. This proposition remains equivocal, even though in vitro studies have reported a phagocytic function for Müller cells [38,39], and ultrastructural studies an increased lysosomal content in the Müller cells of streptozotocin-induced diabetic rats [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies are in line with our observation that Müller cells die in a hyperglycemic environment. The first study to describe dying Müller cells in diabetic retinopathy was done using EM analysis[126]. Dying Müller cells are described as being hypertrophic consistent with the notion that during pyroptosis, cells swell rather than shrink as observed in apoptotic cell death[48].…”
Section: Müller Cell Loss In Diabetic Retinopathymentioning
confidence: 93%
“…On the bad side – Müller cell death will promote loss of retinal blood barrier integrity, increased vascular permeability, and loss of neuroprotection affecting both neurons and vascular cells. Loss of Müller cells in diabetes has also been associated with aneurysm formation, a clinical characteristic of diabetic retinopathy[126]. However, one can also argue that on the good side – removal of activated and pro-inflammatory Müller cells might be a “shut off” mechanism to deal with an increasing inflammatory environment in the diabetic retina.…”
Section: Müller Cell Loss In Diabetic Retinopathymentioning
confidence: 99%
“…Previous studies have shown that after 7 months of diabetes, Müller cells are lost in the retinas of diabetic mice 16 and that Müller cell loss is associated with programmed cell death. 1719 In vitro studies have shown that HG promotes Müller cell apoptosis by decreasing Akt activity. 20 Taken together, these studies provide evidence for Müller cell loss in the diabetic retina.…”
mentioning
confidence: 99%